BASLAWÍSH KLASS OQÍWSHÍLARÍN KLASSTAN TÍS JUMÍSLARDA MIYNET ISLEWGE ÚYRETIW MÁSELELERI - Bazarbaeva, M.A. (SCIENCE and SOCIETY, 2023)
The article reveals the pedagogical problems of teaching schoolchildren in team working while.
Keywords: upbringing; extracurricular activities; labor; class; labor education; movement